2011
DOI: 10.4103/0974-2069.84668
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency presenting with cardiogenic shock in an infant

Abstract: A 2-month-old child was referred as a case of dilated cardiomyopathy with cardiogenic shock. On evaluation, hypocalcemia secondary to severe vitamin D deficiency was found. There were no clinical or radiological features of rickets. The child had developed multiorgan failure due to cardiogenic shock at the time of admission and could not be saved despite adequate ventilatory and pharmacologic support. Hypocalcemia should be considered as an important differential diagnosis in cases of dilated cardiomyopathy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
(8 reference statements)
0
12
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] In contrast to previous cases reported in the literature, we observed improvements in cardiac morphology and functions within 1 week. Patients generally recover from heart failure with anticongestive treatment, positive inotropic support, as well as vitamin D and calcium supplementation and show significant cardiac improvement within a few months.…”
contrasting
confidence: 79%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] In contrast to previous cases reported in the literature, we observed improvements in cardiac morphology and functions within 1 week. Patients generally recover from heart failure with anticongestive treatment, positive inotropic support, as well as vitamin D and calcium supplementation and show significant cardiac improvement within a few months.…”
contrasting
confidence: 79%
“…9,10 There is a growing body of research on the etiology and treatment of dilated cardiomyopathy in children. [1][2][3][4][5][6][7][8] Our patient, who developed dilated cardiomyopathy as a result of hypocalcemia secondary to vitamin D deficiency, received treatment of heart failure as well as calcium and vitamin D replacement. 11 Recently, several cases of dilated cardiomyopathy and heart failure secondary to hypocalcemia resulting from vitamin D deficiency have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…(3, 4) In human infants, recent case reports/series demonstrate that vitamin D deficiency and the resulting hypocalcemia are associated with cardiogenic shock that resolves with vitamin D and calcium repletion. (57) These studies provide support that vitamin D may play a role in myocardial contractility. Adult studies have shown that vitamin D deficiency is associated with a significant risk of cardiovascular disease and reduced survival, and vitamin D supplementation in those with documented deficiency was associated with improved survival.…”
mentioning
confidence: 71%
“…(24) Furthermore, reports of heart failure secondary to vitamin D deficiency and hypocalcemia have been reported in human infants. (57) Recently, a randomized placebo control trial of vitamin D supplementation in 80 infants with congestive heart failure was reported. (26) Infants receiving vitamin D supplementation had greater improvements in clinical symptoms and echocardiographic measurements of ventricular size and function.…”
Section: Discussionmentioning
confidence: 99%
“…In the two largest case series, most [40] or all [41] infants with dilated CMP also had rickets, whereas in others there were apparently no clinical signs of rickets, or no x-rays taken [42,43]. Some of these infants had presented with hypocalcaemic seizures [43] or cardiogenic shock [44,45]. In all reports, infants were from darkskinned ethnic background, were breastfed, and their 25OHD levels were in the deficiency range, with typical biochemical markers associated with rickets [40e47].…”
Section: Hypocalcaemic Dilated Cardiomyopathymentioning
confidence: 89%